Palavras que fazem sangrar: mulheres negras egressas do sistema prisional em João Pessoa/PB - Santos, Anna Paula Batista dos (2024)
This work arose from concerns arising from my professional work with people released from the prison system in João Pessoa/PB and its main objective was to analyze the life stories of black women who left prison and are users of the Social Office, a service that operates to serve this specific audience. The specific objectives were: Verify how the coloniality of power and intersectionality are functional to explore the conditions in the lives of black women released from prison; identify and unravel the issues present in the research field; examine how the elements of violence and resistance are present in women's accounts and understand how the 'life of crime', experiences in prison, religiosity and family relationships constitute fundamental elements in their life stories. Initially, I presented the theoretical and methodological basis that I used to construct this thesis, using mainly the coloniality of power as a theory and intersectionality as an analytical tool. For the data collection procedure, I used in-depth interviews to access the women's memories. Afterwards, I discussed the field in which this research was designed, as well as all the bureaucratic procedures that were necessary for its effective execution and the profile of the women I had access to in this process. Next, I brought up the elements of violence and resistance as crucial and which exist simultaneously in the lives of the researched public, in the most varied forms, namely: sexual and physical violence, in the workplace, transphobia, fatphobia, institutional violence, matriarchy of misery and resistance mainly from the moment of the extinction of penalties in their trajectories. Subsequently, I discussed the women's experiences in the 'life of crime, elements relating to their passage through the prison system, the influence of religiosity in their lives, mainly the evangelical religion of a neo-Pentecostal aspect and their family relationships. The results indicate that intersectional oppressions are present in their trajectories that mean that these women have similar elements in their stories that connect them and that place them as targets for imprisonment, but also that their life experiences are not limited to this, on the contrary, there is potential and desire that moves and encourages them to seek new paths after the period of imprisonment; that neo-Pentecostal religiosity has a great influence on their lives mainly due to the predominance that this aspect reaches in the prison universe and the presence of fatphobia as an element of prejudice and violence in their experiences.